Early salvage radiotherapy in patients with biochemical recurrence after radical prostatectomy: Its impact and optimal candidate. Issue 4 (9th June 2020) - Tomita, Natsuo; Uchiyama, Kaoru; Mizuno, Tomoki; Imai, Mikiko; Sugie, Chikao; Ayakawa, Shiho; Niwa, Masanari; Matsui, Tooru; Otsuka, Shinya; Manabe, Yoshihiko; Nomura, Kento; Kondo, Takuhito; et al.
Abstract: Aim: We aimed to identify the optimal candidates for early salvage radiotherapy (SRT) among patients with biochemical recurrence (BCR) after radical prostatectomy (RP). Methods: This multi‐institutional retrospective study included 371 patients treated using SRT after RP. The median (range) PSA level at BCR was 0.36 (0.10‐2.00) ng/mL. The association between early SRT (ie, starting PSA level < 0.50) and BCR after SRT was tested in each subgroup according to our own risk stratification. Results: The median follow‐up time was 51 months. By multivariate analysis, pT3b, Gleason score ≥ 8, negative surgical margins, PSA doubling time < 6 months, and non‐early SRT were associated with BCR after SRT. Patients were stratified by four risk factors other than non‐early SRT: (1) low risk (0 risk factor), (2) intermediate risk (1 risk factor), and (3) high risk (≥2 risk factors). The BCR‐free survival was higher in the early SRT group than the nonearly SRT group in the high‐risk subgroup ( P  = 0.020), whereas that was similar between two groups in the low‐risk and intermediate‐risk subgroups ( P  = .79 and .18, respectively). Multivariate analysis revealed that early SRT was beneficial for the high‐risk subgroup ( P  = .032), whereas early SRT was not associated with improved outcomes in the low‐risk and intermediate‐risk subgroups ( P  = .92 and 1.0, respectively). Conclusions: This study suggested that early SRT seemed to contribute to better biochemical control for patients with more adverse features, whereas no benefit was observed in men with no adverse features.